Analisis Penilaian Faktor-Faktor Daya Tarik Pengunjung di Desa Wisata Bojongkulur Kecamatan Gunungputri Kabupaten Bogor - Rianto, Rianto; Nurmalinda, Elda; Na, Quan (Jurnal Ilmiah Pariwisata, 2024)
This research was conducted to determine the factors of visitors who come to the Bojongkulur Tourism Village, Bogor Regency. This village is one of the villages that initially every rainy season always experiences environmental problems, namely flooding problems, namely in the Block KD Vila Nusa Indah 3 RT 06 RW 36 area which borders the Cikeas river. This research uses a quantitative descriptive method to measure tourist attraction factors in the Bojongkulur tourist village, using a Cartesian diagram analysis tool. Based on the results of a questionnaire with 80 respondents to assess 8 assessment factors based on visitors' expectations and reality, 7 indicators were produced, including culture in its various forms, rivers with all their attractions, travel comfort, extensive opportunities to relax. The image, natural beauty and friendliness of the people are considered to have met visitors' expectations. Based on Cartesian diagram analysis, it reaches an average value of 4.2. Meanwhile, the tourist product price indicator is still assessed by visitors and still does not meet the figure of 2.9. This means that these 8 attractiveness factors are still considered lacking by visitors. In the researcher's analysis, this is caused by the accessibility of river tourism activities in the Bojongkulur tourist village, the route is short and only has one attraction, this is considered not commensurate with the costs incurred . Keywords: Bojongkulur tourist village, 8 indicators of attractiveness, cartesian diagram